Diagnóstico do uso do solo em APP na microbacia do córrego Santo Antonio - São Manuel (SP) em função da legislação ambiental - Campos, Sérgio [UNESP]; Pupo, Gabriel Rondina da Silveira [UNESP]; Pissarra, Tereza Cristina Tarlé [UNESP]; Felipe, Andrea Cardador [UNESP]; Garcia, Yara Manfrin [UNESP]; Campos, Mariana de [UNESP] (My University, 2013)
The present work sought to the geotecnology use in the mapping of soil use in areas of PPA's, allowing their delimitations and diagnosis of possible humane interventions. The watershed with 4286,15ha, locates among the geographical coordinates 22o 31' 52" to 22o 38' 20" of latitude S and 48o 33' 40" to 48o 38' 47" of longitude WGr. The used cartographic bases were the planialtimetric chart for the georreferencing of the satellite image of 2011. GIS-IDRISI Selva was used in the supervised classification and the determination of the areas of the thematic map. The soil use showed that the culture of the sugar-cane occupies most of the area (81%), showing with that the predominance of the agricultural occupation in the area. The image and the use of GIS important tools were shown, supplying reliable results in a small interval of time. The obtained data will aid in the futures plannings of recovery of the area, because they made possible the verification that the area is not being preserved environmentally, link fact of presenting only 12,54% of forests, and the minimum demanded by the legislation of the Brazilian Forest Code effective is of 20%.

O presente trabalho visou à utilização de geotecnologias no mapeamento de uso da terra em áreas de APP’s, permitindo as suas delimitações e diagnóstico de possíveis intervenções antrópicas, contribuindo para futuras fiscalizações ambientais. A microbacia com 4286,15ha, situa-se entre as coordenadas geográficas 22o 31’ 52” a 22o 38’ 20” de latitude S e 48o 33’ 40” a 48o 38’ 47” de longitude WGr. As bases cartográficas utilizadas foi a carta planialtimétrica para o georreferenciamento da imagem de satélite de 2011. O SIG-IDRISI Selva foi utilizado na classificação supervisionada e a determinação das áreas do mapa temático. O uso da terra mostrou que a cultura da cana-de-açúcar ocupa a maior parte da área (81,00%), mostrando com isso a predominância da ocupação agrícola na região. A imagem de satélite e a utilização do SIG mostraram-se importantes ferramentas, fornecendo resultados confiáveis num pequeno intervalo de tempo. Os dados obtidos auxiliarão nos futuros planejamentos de recuperação da área, visto que possibilitaram a verificação de que a área não vem sendo ambientalmente preservada, pelo fato de apresentar apenas 12,54% de matas, sendo que o mínimo exigido pela legislação do Código Florestal Brasileiro vigente é de 20%.
Diagnosis of the soil use in APP of the stream Santo Antonio watershed - São Manuel (SP) in function of the environmental legislation
Keywords: Environmental legislation; Geographical information system; Environmental preservation; Legislação ambiental; Sistema de informação geográfica; Preservação ambiental